2022
DOI: 10.18203/2349-2902.isj20222939
|View full text |Cite
|
Sign up to set email alerts
|

Validation of intra-operative scoring system for difficult laparoscopic cholecystectomy

Abstract: Background: Laparoscopic cholecystectomy is the procedure of choice for most patients with gallbladder disease. The key, as in open surgery, is the identification and safe dissection of Calot’s triangle. Surgeons performing laparoscopic cholecystectomy should not think of conversion to open operation as a complication, but rather a sound clinical judgment.Methods: This is an observational, single center study. The scoring system included five aspects; appearance and adhesion of gall bladder (GB), distension or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…Using a prospective approach to analyse all grades on the Nassar scale, we sought to achieve consistent and reliable results, in order to investigate the practical application of this scale in our clinical practice. Gupta et al 9 defined surgeries as difficult if it took more than 60 minutes to complete the cholecystectomy, which is consistent with our findings, suggesting that the longer duration of surgery correlates with higher Nassar grades. Kemal et al 10 used the duration of the operation to classify the severity of cholecystectomy, dividing these operations into "difficult" and "very difficult" according to the duration of the cholecystectomy and complicating factors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Using a prospective approach to analyse all grades on the Nassar scale, we sought to achieve consistent and reliable results, in order to investigate the practical application of this scale in our clinical practice. Gupta et al 9 defined surgeries as difficult if it took more than 60 minutes to complete the cholecystectomy, which is consistent with our findings, suggesting that the longer duration of surgery correlates with higher Nassar grades. Kemal et al 10 used the duration of the operation to classify the severity of cholecystectomy, dividing these operations into "difficult" and "very difficult" according to the duration of the cholecystectomy and complicating factors.…”
Section: Discussionsupporting
confidence: 91%
“…Emergency patients had significantly higher Nassar grades compared to patients undergoing elective surgery. While no studies comparing Nassar grade levels based on the type of surgical indication for cholecystectomy were found, previous research indicated a potential connection between complications during laparoscopic cholecystectomy and variations in C-reactive protein (CRP) levels, with notable discrepancies in CRP values and conversion criteria across different studies1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14] . While our study did not specifically investigate the relationship between CRP levels and conversion, this aspect warrants attention in future research to understand better how CRP may be linked to the Nassar scale.…”
Section: Discussionmentioning
confidence: 99%